Analisis Konsep Fisika pada Penyinaran Buah Naga - Arinda Salsa Bella; Zilfiyatul Makida; Sudarti Sudarti; Kendid Mahmudi (Jurnal Kridatama Sains dan Teknologi, 2026)
Artificial lighting in dragon fruit cultivation involves several physics concepts, particularly light intensity, wavelength, lighting duration, energy conversion, and sensor-based lighting control systems. Among these concepts, this article focuses on light intensity, LED wavelength, lighting duration, and the use of light sensors in automation systems. Dragon fruit (Hylocereus spp.) is a prickly cactus plant originally from Central America and is now widely cultivated in Indonesia. One of the main challenges in dragon fruit cultivation is the limited flowering and fruiting season, which occurs only during certain periods. This study aims to analyze the application of physics concepts in artificial lighting systems to improve the productivity and quality of dragon fruit. The method used in this study is a literature review of relevant previous research. The findings indicate that the use of LED lamps with specific light intensities and wavelengths can stimulate photosynthesis, flowering, and the formation of bioactive compounds such as flavonoids and anthocyanins. In addition, the use of light sensors, solar panels, and Internet of Things-based systems supports energy efficiency and automatic lighting control. Therefore, the application of physics concepts in dragon fruit lighting plays an important role in the development of productive and sustainable smart agriculture.